Comparison between RVE and full mesh approaches for the simulation of compression tests on cellular metals - Oliveira, B. F.; Cunda, L. A. B.; Ochsner, Andreas; Creus, G. J. (Wiley-Vch, 2008)
Metal foams are materials of recent development and application that show interesting combinations of physical and mechanical properties. Many applications are envisaged for such materials, particularly in equipments of passive safety, because of their high capacity of energy absorption under impact conditions. The damage analysis in metallic foams is a complex problem and must be performed in a finite strain context. Considering that compression is the dominant loading in impact situations, a finite deformation simulation including damage effects of a compression test on a cellular metal sample is shown in this work. The main objective of the paper is to compare simulations considering periodic boundary conditions, by means of a representative volume element (RVE) approach, with results obtained using full meshes. It is shown that, when the imposed deformation is high, the use of RVE does not describe in a proper manner the deformation that occurs at the walls of cells. This characteristic of RVE approach results in a too stiff behavior when considering load-displacement relations. A comparison with experimental results is also presented.